Monumental Jesus : Landscapes of Faith and Doubt in Modern America - Grubiak, Margaret M. (Book collections on Project MUSE., 2020)
"This book explores how religious doubt is made manifest in the built environment by taking seriously the humorous, satirical, blasphemous, and popular culture responses to religious architecture and image in modern America. It challenges how audiences typically consider religious architecture by shifting the focus from believers to doubters and from architectural producers to architectural consumers. Its chapters explore landscapes of doubt created by "Touchdown Jesus" at the University of Notre Dame in Indiana; the Mormon temple outside Washington, D.C., recast as something from The Wizard of Oz; Jerry Falwell's waterslide plunge photograph and The Simpson's "Praiseland" episode satirizing Jim and Tammy Faye Bakker's Heritage USA evangelical theme park in South Carolina; the doctored photograph making fun of Oral Roberts's claim of seeing a 900-foot Jesus at Oral Roberts University in Tulsa, Oklahoma; MAD magazine's "Charles Darwin's Night at the Creation Museum" parody of the Creation Museum in Kentucky; and the "Gumby Jesus" renaming of the Christ of the Ozarks statue in Eureka Springs, Arkansas. These expressions of doubt activate the religious built environment in ways unanticipated but illuminating, asking Americans to consider and clarify what it is they believe"--